Patent disputes as emerging barriers to technology entry? Empirical evidence from patent opposition - Arianna Martinelli; Julia Mazzei; Daniele Moschella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
The recent surge of patent disputes plays an important role in discouraging firms from entering new technology domains (TDs). Using a large-scale dataset combining data from the EPO-PATSTAT database and ORBIS-IP and containing patents applied at EPO between 2000 and 2015, we construct a new measure of litigiousness using patent opposition data. We find that the degree of litigiousness and the density of patent thickets negatively affect the likelihood of firms entering new TDs. Across technologies, the frequency of oppositions discourages firms mostly in high-tech industries. Across firms, the risk of opposition falls disproportionately on small rather than large firms. Finally, for large firms, we observe a sort of learning-by-being-opposed effect. This evidence suggests that litigiousness and hold-up potential discourage firms from entering new TDs, shaping Schumpeterian patterns of innovation characterized by a stable number of large-established firms and a lower degree of turbulence.
Keywords: O31; O33; O34; 330; Patent opposition; Technological entry; Innovation Strategies